Turkish Validity and Reliability Study of the Intrinsic Spirituality Scale - Bahçecioğlu Turan, Gülcan; Yanmiş, Safiye; Özer, Zülfünaz (AVES, 2022)
Objective: This study was conducted to adapt “The Intrinsic Spirituality Scale (ISS)” into Turkish and to find out its validity and reliability. Material and Methods: This methodological study was carried out with 289 individuals aged 18 and older who were reached online (e-mail, whatsapp, facebook, and instagram) between September 10 and 30, 2020. The questionnaire form prepared via docs.google.com/forms was sent online to individuals (e-mail and whatsapp). The items of the scale are scored between 0 and 10 and the scale has 6 items. Following the translation process of the scale, content and construct validity were assessed. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were performed for construct validity, while item analyses and internal consistency analysis were performed for reliability. Results: As a result of the evaluations and analyses conducted, content validity index of the scale was found as 0.99. Total Cronbach’s alpha coefficient of the scale was found as 0.90. Item loads were found to be between 0.71 and 0.90 and item-total correlation coefficients were found to be between 0.61 and 0.79. The results of EFA and CFA confirmed the single factor structure of the scale. Good fit indices were found as a result of CFA. Conclusion: Turkish version of the “ISS” is a valid and reliable measurement tool to evaluate the degree of motivation of the individual by his/her spirituality, which is also defined as his/her relationship with God. © 2022 Archives of Health Science and Research. All rights reserved.
Keywords: Intrinsic spirituality scale; Nursing; Reliability; Validity